Assessing the Effectiveness of Cognitive Behavioral Stress Management (CBSM) on Anxiety and Depression of Cancer Patients - Asadbeygi, Ali; Ahadi, Hasan; Mirzai, Hamid Reza (Novelty in Biomedicine, 2018)
Background: The purpose of this study was to determine the effectiveness of cognitive-behavioral stress therapy on stress, depression and distress in patients with cancer. Cases Report: In a cross-sectional study of consecutive patients (Aged 32-70 years, progression of their disease was at levels 1 to 3, high cycle education, and 3 months of chemotherapy, of which 40, were randomly available from this group (20 experimental and 20 Control group). The instrument was a McGill Pain Questionnaire (1997) and the Hazards and Anxiety and Depression Scale (HADS) questionnaire. Data were analyzed using two methods of Kolmogorov-Smirnov inferential statistics and multivariate analysis of covariance using software software Spss17. Conclusion: Correlation analysis showed that the experimental group had a significant reduction in depression and anxiety in the posttest after the control group compared with the control group. The short-term cognitive-behavioral stress management program can reduce, depression and anxiety in cancer patients.